Propagation and Feasibility Study of Pennisetum purpureum for Removal of Arsenic in Constructed Wetland (Journal of Environmental Microbiology and Toxicology, 2023)
Various species of plants have recently been identified as hyperaccumulators, capable of storing and resisting high concentrations of toxic metals. A perfect hyperaccumulator for phytoremediation must exhibit rapid growth and produce significant biomass. In the case of P. purpureum, roots displayed a growth rate of 1.19 cm/day, stems 4.78 cm/day, with an absolute growth rate (AGR) peaking at 4.16 ± 0.091 gm/day after 77 days. Regression analysis (y = 0.138x, R2 = 0.9904) revealed a strong correlation between dry and wet weights. Water content in P. purpureum ranged from 70.59 ± 1.27% to 85.54 ± 1.54%. Typically propagated from seeds, P. purpureum is known for its ease of cultivation, rapid growth, and simple seed collection for subsequent generations. At 77 and 105 days, respective calorific values for the whole plant were 19,888 ± 238.66 J/g and 18,405 ± 220.86 J/g, indicating potential bioenergy use post-phytoremediation. This study comprehensively examines the physical growth, growth rate, biomass, water content, and calorific value of P. purpureum, revealing its robust root system and rapid growth characteristics. Thus, P. purpureum emerges as a promising candidate for heavy metal uptake in environmental remediation efforts.
Keywords: Biomass; Pennisetum purpureum; Phytoremediation; Linear regression analysis; Calorie